PENILAIAN KINERJA SDM DENGAN PENDEKATAN HUMAN RESOURCE SCORECARD - Urika MM (LPPM Universitas Banten jaya, 2020)
The problem of human resources is currently still the center of attention and a focus for an organization or company to be able to survive in the era of globalization accompanied by increasingly fierce levels of competition. The problem often faced by companies is the absence of a performance measurement system that is able to support the role of HR towards company strategy. Human Resource Scorecard is a method used to measure the contribution of HR. The HR Scorecard is also the development of the Balanced Scorecard Performance appraisal through the HR Scorecard approach can be a high-level performance indicator (Key Performance Indicator / KPI) of the HR management function. The true HR Scorecard allows the HR function to perform 2 important functions at the same time: (1) managing HR as a strategic asset; and (2) demonstrating the contribution of HR to the financial success of the company.